Essay as academic writing and the production of projects and research - Dahmer, Carin Cristina; Neuscharank, Angélica; Oliveira, Marilda Oliveira de (Historia y Memoria de la Educación, 2019)
This article proposes to think of academic writing from experiences with research orientations in a teacher training course in visual arts, from the state of Rio Grande do Sul, Brazil. In this way, it is sought to share some concerns produced in the middle of the writing processes of teaching and research projects and final graduate work. It was chosen to compose the theoretical questions the interweaving of some studies from what Pereira proposes about the uses of words, as a political arena, a weapon and a negotiating effect; the terrors of a hegemonic form of writing in the academy, punctuated by Silva; the proposal of the essay as written and the experience with Larrosa, as well as the notion of text-reading pointed out by Barthes that is based on what the reader produces of senses when reading a text. As a method, it was thought possible experiments of a writing-essay, that perpass other ways of writing, betting on literature and the art like variations for the academic writing. In this sense, we conclude that the contribution of a research in the field of visual arts education does not need to propose a transformation in the research spaces, or in the collaborators, but that it can produce effects in the researcher, when producing senses for him/her. We propose that academic spaces can accommodate other forms of writing that are organized in different ways, be it in relation to its format or the use of images as text tensors, producing knowledge and problematizing the field of research and education.